Model Predictive Stator Flux Control of Permanent Magnet Synchronous Motor Based on Vector Duty Ratio Modulation - Jing He; Zongyu Li; Gongping Wu; Runzhong Tang (IEEE Access)
To address the issues of extensive computation and laborious weight coefficient selection in model predictive torque control (MPTC) for permanent magnet synchronous motors (PMSM), an optimized model predictive flux control (MPFC) is proposed based on three-phase voltage vector duty ratio modulation. First, we established a prediction model of PMSM based on stator flux linkage, constructed a prediction error cost function of stator flux linkage without weight coefficient. Meanwhile, the duty ratio of neighboring voltage vectors in each sector and the stator flux reference value were computed using the stator flux deadbeat control concept, and the stator flux reference value is computed. Finally, we proposed an optimal stator flux predictive control method based on three-phase voltage vector duty ratio modulation. Its effectiveness and reliability were verified by simulation and experiment. This method had excellent steady-state performance in the voltage vector output range, requires fewer predictions than the classic model predictive torque control method, and greatly reduces both the stator flux and the electromagnetic torque ripple.